A clarification of the distinctions between Pleurothallis talpinaria and Pleurothallis trimeroglossa (Orchidaceae: Pleurothallidinae) and an allied new species from Ecuador - Wilson, Mark (2017)
Pleurothallis trimeroglossa has long been considered a synonym of P. talpinaria. In this study we reviewed types, descriptions, drawings, paintings and living material for both names and concluded that P. talpinaria and P. trimeroglossa should be recognized as distinct species. An anatomical structure important in the distinction between the two is the large dome-shaped callus at the base of the lip in P. trimeroglossa. The approximate distributions and elevational ranges of the two species are discussed. During the study we recognized a novel species, described here as Pleurothallis jostii. Labellar morphology of all three species was examined. We speculate on the pollination mechanism of this group of species based on the observations of labellar micro-morphology.